2017
DOI: 10.1108/bfj-06-2016-0284
|View full text |Cite
|
Sign up to set email alerts
|

Importance of intrinsic and extrinsic quality food characteristics by different consumer segments

Abstract: Purpose The purpose of this paper is to examine intrinsic and extrinsic food quality characteristics and the relative importance placed on these characteristics by different consumer segments. Moreover, relationship between segments of consumers and consumption frequency of differentiated food products (traditional, functional and organic) was analysed. Design/methodology/approach A three-stage stratified random sampling approach was employed and data were collected via 500 face-to-face interviews conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 71 publications
7
66
1
1
Order By: Relevance
“…The difference from the present research consists of the number of tested cues (their study tested nine quality elements) and the fact that it identified two consumer groups according to the quality cues that they used. Brecic et al [25] analyzed the importance of quality cues to consumers, but the number of cues investigated in their study was lower compared to the number of cues tested in the present study (20 vs. 59).…”
Section: Introductioncontrasting
confidence: 58%
“…The difference from the present research consists of the number of tested cues (their study tested nine quality elements) and the fact that it identified two consumer groups according to the quality cues that they used. Brecic et al [25] analyzed the importance of quality cues to consumers, but the number of cues investigated in their study was lower compared to the number of cues tested in the present study (20 vs. 59).…”
Section: Introductioncontrasting
confidence: 58%
“…This indicates that this cluster is merely concerned with using tomato as an essential ingredient for meal preparation (Table 4). Brečić et al (2017) and Kovačić et al (2010) also identified similar consumer segments who did not care about most of the quality attributes of fresh produce.…”
Section: Segments Of Tomato Consumersmentioning
confidence: 94%
“…One relevant observation is that consumer behavior studies, in general, tend to include intrinsic and extrinsic values in one way or the other, but these attributes are quite absent in the wider local food discussion, except for some recent articles [29]. Thus, the relevance of intrinsic and extrinsic attributes highlighted in this case helps us to enrich our understanding of consumers in market-driven direct produce systems and close typicity systems.…”
Section: Intrinsic and Extrinsic Attributesmentioning
confidence: 96%
“…However, consumers can also be driven by so-called extrinsic attributes; that is, attributes disconnected from the product, but connected to the sale. Some examples of such attributes are brand name, brand image, stamp of quality (for example, an ecological brand, or a protected designation of origin), price, country and/or place of origin, store, staff at the selling point, packaging, production information, and consumer communication [29][30][31].…”
Section: Intrinsic and Extrinsic Product Attributesmentioning
confidence: 99%
See 1 more Smart Citation